Pancreatic neuroendocrine tumors: A review of serum biomarkers, staging, and management - Ma, Zu-Yi; Gong, Yuan-Feng; Zhuang, Hong-Kai; Zhou, Zi-Xuan; Huang, Shan-Zhou; Zou, Yi-Ping; Huang, Bo-Wen; Sun, Zhong-Hai; Zhang, Chuan-Zhao; Tang, Yun-Qiang; Hou, Bao-Hua (World journal of gastroenterology : WJG, 2020)
Pancreatic neuroendocrine tumors (pNETs) are a heterogeneous group of tumors with complicated treatment options that depend on pathological grading, clinical staging, and presence of symptoms related to hormonal secretion. With regard to diagnosis, remarkable advances have been made: Chromogranin A is recommended as a general marker for pNETs. But other new biomarker modalities, like circulating tumor cells, multiple transcript analysis, microRNA profile, and cytokines, should be clarified in future investigations before clinical application. Therefore, the currently available serum biomarkers are insufficient for diagnosis, but reasonably acceptable in evaluating the prognosis of and response to treatments during follow-up of pNETs. Surgical resection is still the only curative therapeutic option for localized pNETs. However, a debulking operation has also been proven to be effective for controlling the disease. As for drug therapy, steroids and somatostatin analogues are the first-line therapy for those with positive expression of somatostatin receptor, while everolimus and sunitinib represent important progress for the treatment of patients with advanced pNETs. Great progress has been achieved in the combination of systematic therapy with local control treatments. The optimal timing of local control intervention, planning of sequential therapies, and implementation of multidisciplinary care remain pending.